Calling Party Pays or Receiving Party Pays? - Ralf Dewenter; Jörn Kruse (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2005)
This paper analyzes the impact of different payment regimes for mobile-to-mobile off-net calls on the diffusion of mobile telephony, using data on 84 countries from all over the world. Since the decision whether or not countries are likely to switch from RPP to CPP is not independent from penetration rates, a problem of endogenous regulation arises. In order to account for this problem we refer to data on political and democratic stability to instrument endogenous policy decisions. However, positive effects from regime switching seem to vanish when accounting for endogenous regulation. The effects of introducing competition instead seems to be underestimated ignoring endogeneity.
urn:nbn:de:gbv:705-opus-16546
Keywords: 330; Mobilkommunikation; Telekommunikationsgebühr; Telekommunikationspolitik; Mobiltelefon; Innovationsdiffusion; Schätzung; Theorie; Welt